Análise elementar dos cosméticos: esmaltes de unha e argilas - Narloch, Danielle Cristine (2021)
In Brazil, The Brazilian Health Regulatory Agency (ANVISA) defines cosmetics as being composed of natural or synthetic substances, which are applied to the external surface of the human body. In the Resolution RDC No. 83 of 28 June 2016 there are 1373 prohibited substances in personal hygiene products, cosmetics and perfumes, based on the list of prohibited substances in the European Union document. Elements such as Cl, Ni, As, Be, Cd, Cr, I, P, Pb, Hg, Se, Zr, Co, Te, Tl and radioactive substances are present in the list. Canadian legislation establishes that toxic elements such as Pb, As, Cd, Hg and Sb should not be used as ingredients. The objective of this work was to characterize and quantify the chemical elements present in nail polishes and cosmetic clays by means of some instrumental analytical techniques. Measurements of the samples with the equipment of EDXRF of AMPTEK were performed. This equipment model MINI-X contains two detectors silicon drift, model 123SDD. Other analyzes of these samples were carried out using the Scanning Electron Microscope (SEM) together Dispersive Energy Spectrometer (DES), both Zeiss brand, EVO MA 15 model and Shimadzu XRD 7000 X-Ray Diffractometer (XRD). In addition to these techniques some clays were subjected to gamma spectrometry analysis at the Nuclear and Energy Research Institute (IPEN) to verify the radionuclides present. Obtained results indicated the presence of the following elements in the nail polishes analyzed: Mg, Al, P, Si, S, Cl, Ca, Ti, Cr, Mn, Fe, Ni, Cu, Zn, Ba and Bi. The cosmetic clays presented the Mg, Al, P, As, Se, Ba, Co, Si, S, Cl, K, Ca, Ti, Mn, Sb, Fe, Ni, Cu, Zn, Rb, Zr, Sr, Th, U, Pb and Ra elements. Some detected elements are prohibited and restrictive according to ANVISA and international legislation such as As, Cl, P, Cr, Sb, Ni, Zr and Pb. The bioaccumulation of these substances in the body can cause metabolic disorders.